Appraisal Attitude Analysis of Aljazeera’s and BBC’s News Entitle: Israeli Attacks on Gaza Schools Issues - Elvira Putri Anshary; Aprilza Aswani; Muhammad Yusuf (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This study focuses on the attitude framework to explore differences between two media sources, aiming to determine if they have different perspectives on the same recent issue or share similar opinions. The article was analyzed based on an attitude framework consisting of appreciation, affect, judgment, and amplification based on Eggins & Slade’s theory and Martin & Slade’s theory. The data were analyzed in a qualitative approach. The findings found that that 60 lexical items in Aljazeera and 26 lexical items found in BBC that can be categorized in attitude. As it can be seen from the total of both Aljazeera and BBC, Appreciation has the higher number in attitude with 43% and 50%. The findings show that how news media strategically employ language to shape perceptions and engage audiences, adapting their linguistic strategies to effectively convey attitudes and viewpoints on current affairs.